2021
DOI: 10.1029/2020gh000294
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Antibiotic Resistance Profiles of Salmonella enterica in Rural Areas of North Carolina After Hurricane Florence in 2018

Abstract: The frequency and magnitude of extreme events are increasing globally (Arnell & Gosling, 2016). Inundation, as a result of massive flooding, has the potential to change environmental conditions abruptly, and as a result, add pressure to the metabolism and proliferation of microorganisms (Furtak et al., 2020). The resulting overland flows and additional burden from domestic sewer and septic tank systems during an extreme flood event can introduce pathogens into ecologically unstable water bodies. For example, Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
8
1
Order By: Relevance
“…In this study, we found no simple correlation between the presence of S. enterica and proximity to flooded swine farms, or between culturable Salmonella and the quantity of the Salmonella ttrC genetic marker (data shown previously in Mao et al (2021)). In the places we sampled, we found S. enterica to be from environmental sources.…”
Section: Discussioncontrasting
confidence: 54%
“…In this study, we found no simple correlation between the presence of S. enterica and proximity to flooded swine farms, or between culturable Salmonella and the quantity of the Salmonella ttrC genetic marker (data shown previously in Mao et al (2021)). In the places we sampled, we found S. enterica to be from environmental sources.…”
Section: Discussioncontrasting
confidence: 54%
“…MDR Salmonella strains are currently spreading in the human food supply chain and have a huge impact on economics and health ( Tasmin et al, 2019 ; Castro-Vargas et al, 2020 ; Chen et al, 2020 ). This concern raised the alarm on the need to find alternative ways to control this important foodborne pathogen ( Kongsanan et al, 2020 ; Mao et al, 2021 ; Sargun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella Typhimurium (ST) is a gram negative enteric pathogen 43 which enters human gut through consumption of contaminated food or drink. An increase in antibiotic resistance strains of ST raised the concern and developed the need to find alternative prophylactic and therapeutic agents to control this important gastrointestinal pathogen [44][45][46] . S.…”
Section: Resultsmentioning
confidence: 99%